2021
DOI: 10.1016/j.onehlt.2021.100249
|View full text |Cite
|
Sign up to set email alerts
|

Domestic pig prioritized in one health action against fascioliasis in human endemic areas: Experimental assessment of transmission capacity and epidemiological evaluation of reservoir role

Abstract: The Northern Bolivian Altiplano is the human fascioliasis hyperendemic area where the highest prevalences and intensities in humans have been reported. Preventive chemotherapy was implemented in the last ten years. Surveillance showed high human infection and re-infection rates in between the annual triclabendazole monodose treatments. A complementary One Health control action was launched to decrease the infection risk. Among the multidisciplinary axes, there is the need to establish animal reservoir species … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 92 publications
0
16
0
Order By: Relevance
“…In Egypt, subjects were treated after active detection by qualitative coprological diagnosis with the fast and simple Kato-Katz technique [ 29 , 30 ], by the survey teams of the Ministry of Health and Population (MoHP) located throughout the endemic rural areas and already working on another freshwater snail-borne trematodiasis such as schistosomiasis [ 31 ]. Moreover, a multidisciplinary One Health intervention is underway to complement preventive chemotherapy in Bolivia, to decrease infection and re-infection risks in between the annual treatment campaigns [ 4 , 6 , 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…In Egypt, subjects were treated after active detection by qualitative coprological diagnosis with the fast and simple Kato-Katz technique [ 29 , 30 ], by the survey teams of the Ministry of Health and Population (MoHP) located throughout the endemic rural areas and already working on another freshwater snail-borne trematodiasis such as schistosomiasis [ 31 ]. Moreover, a multidisciplinary One Health intervention is underway to complement preventive chemotherapy in Bolivia, to decrease infection and re-infection risks in between the annual treatment campaigns [ 4 , 6 , 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Galba truncatula and L. schirazensis are amphibious snails that share the capacity of being passively transported when they remain in dried mud stuck to the feet of ruminants, then go into hibernation or estivation during the drought, and be able to reactivate once in a new location following contact with water [ 4 , 33 ]. The detection of Galba truncatula indicates the freshwater collection to be of risk for liver fluke infection, as it has proved to transmit liver fluke isolates from the different mammal host species in the highlands [ [61] , [62] , [63] ]. The non- transmitting species L. schirazensis has proved to be a useful biomarker for the follow-up of livestock movements and fascioliasis spread, inter- and intra-continentally and also locally [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, terms as outbreak or epidemics [89] should be considered misinterpretations of the transmission and epidemiological situation. Only human action appears to modify given transmission foci, as for instance along the construction of paved roads, implementation of irrigations, and improvement of water sources [48].…”
Section: Characteristics Of the Transmission Focimentioning
confidence: 99%
“…Sheep and cattle have demonstrated that they are able to participate as the main reservoirs, even at such a high altitude [47]. The domestic pig has proven to be the third most important reservoir, despite many previous studies arguing against the potential role of this animal in fascioliasis [48]. The donkey demonstrated that it was the fourth reservoir species involved, with a problematic role in the geographical diffusion of both liver fluke and snail vector [49].…”
mentioning
confidence: 99%